FeCo Nanoparticles Encapsulated in N‐Doped Carbon Nanotubes Coupled with Layered Double (Co, Fe) Hydroxide as an Efficient Bifunctional Catalyst for Rechargeable Zinc–Air Batteries. Issue 44 (22nd September 2021) - Zhang, Tongrui; Bian, Juanjuan; Zhu, Yuanqin; Sun, Chunwen
Abstract: Low‐cost bifunctional nonprecious metal catalysts toward oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are critical for the commercialization of rechargeable zinc–air batteries (ZABs). However, the preparation of highly active and durable bifunctional catalysts is still challenging. Herein, an efficient catalyst is reported consisting of FeCo nanoparticles embedded in N‐doped carbon nanotubes (FeCo NPs‐N‐CNTs) by an in situ catalytic strategy. Due to the encapsulation and porous structure of N‐doped carbon nanotubes, the catalyst shows high activity toward ORR and excellent durability. Furthermore, to enhance the OER activity, CoFe‐layer double hydroxide (CoFe‐LDH) is coupled with FeCo NPs‐N‐CNTs by in situ reaction approach. As the air electrode for rechargeable ZABs, the cell with CoFe‐LDH@FeCo NPs‐N‐CNTs catalyst exhibits high open‐circuit potential (OCP) of 1.51 V, high power density of 116 mW cm −2, and remarkable durability up to 100 h, demonstrating its great promise for the practical application of the rechargeable ZABs. Abstract : Porous carbon nanotubes with embedded FeCo nanoparticles are synthesized by an in situ catalytic strategy. CoFe‐LDH is coupled with them by in situ growth approach. The obtained composite catalyst exhibits superior bifunctional electrocatalytic activity with a Δ E of 0.68 V. It also exhibits remarkable durability up to 100 h with a low voltage gap of 0.69 V as the cathode for zinc–air battery.